PF4/Heparin Antibody Testing and Treatment of Heparin-Induced Thrombocytopenia in the Intensive Care Unit. (June 2013) - Wanat, Matthew; Fitousis, Kalliopi; Hall, Jeff; Rice, Lawrence
Background: The diagnosis of heparin-induced thrombocytopenia (HIT) may be challenging in critically ill patients, as heparin exposures are ubiquitous, and thrombocytopenia is common. Unwarranted ordering and incorrect interpretation of heparin antibody tests can expose a patient to adverse drug events and imposes a significant economic burden on our health care system. Methods: A prospective, observational study was performed over 4 months on all adult patients located in 5 intensive care units, with a heparin antibody test ordered. Results: A platelet factor 4/heparin enzyme-linked immunosorbent assay (ELISA) test was ordered in 131 patients. In total, 110 patients had a low 4Ts score (0-3), and of these 103 had a negative ELISA result. In patients with a low 4Ts score, 0 (0%) of 110 had an optical density value >1.0. One hundred twenty-nine patients (98%) had another possible cause of thrombocytopenia identified. Conclusion: In critically ill patients, low 4Ts scores indicate a low probability of HIT, and heparin antibody testing in these patients is not useful.